Planck observations of M33. Issue 4 (29th March 2018) - Tibbs, C T; Israel, F P; Laureijs, R J; Tauber, J A; Partridge, B; Peel, M W; Fauvet, L
Abstract: We have performed a comprehensive investigation of the global integrated flux density of M33 from radio to ultraviolet wavelengths, finding that the data between ∼100 GHz and 3 THz are accurately described by a single modified blackbody curve with a dust temperature of T dust = 21.67 ± 0.30 K and an effective dust emissivity index of βeff = 1.35 ± 0.10, with no indication of an excess of emission at millimetre/submillimetre wavelengths. However, subdividing M33 into three radial annuli, we found that the global emission curve is highly degenerate with the constituent curves representing the subregions of M33. We also found gradients in T dust and βeff across the disc of M33, with both quantities decreasing with increasing radius. Comparing the M33 dust emissivity with that of other Local Group members, we find that M33 resembles the Magellanic Clouds rather than the larger galaxies, i.e. the Milky Way and M31. In the Local Group sample, we find a clear correlation between global dust emissivity and metallicity, with dust emissivity increasing with metallicity. A major aspect of this analysis is the investigation into the impact of fluctuations in the cosmic microwave background (CMB) on the integrated flux density spectrum of M33. We found that failing to account for these CMB fluctuations would result in a significant overestimate of T dust by ∼5 K and an underestimate of βeff by ∼0.4.